AB0707 IS ANKYLOSING SPONDYLITIS ASSOCIATED WITH INCREASED MALIGNANCY RISK?. (2nd June 2020) - Merjanah, S.; Bittar, M.; Magrey, M.
Abstract : Background: Increased cancer risk has been reported with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Few studies on malignancy risk in ankylosing spondylitis (AS) patients have provided conflicting data. Objectives: To look at the risk of cancer in AS patients in the US and identify any risk factors associated with increased cancer frequency. Methods: This is a retrospective observational study using the IBM Explorys data base, a pooled de-identified clinical data base of > 60 million unique patients in the US with patient level data. The Explorys collects aggregated, standardized and normalized clinical data from different electronic health records automatically updated in near real time. In Explorys, patient records are mapped into a single set of Unified Medical Language System ontologies to facilitate searching and indexing. Diagnoses, findings and procedures are mapped into the systematized nomenclature of medicine – clinical terms (SNOMED-CT) hierarchy. Criteria of AS included at least one visit with a rheumatologist and the diagnosis code of AS (N=14, 310) between 2009-2019. We further stratified the cohorts by adding the following variables to the search tool: race, gender, smoking, laboratory data (elevated ESR and CRP, HLA-B27 status), extra articular manifistations (psoriasis, inflammatory bowel disease or uveitis) and medication use (TNF inhibitor, secukinumab or NSAIDs). The index date was defined as the date of the first ever malignant neoplastic disease diagnosis occurring after the qualifying AS diagnosis. The controls group (24, 542, 770) included all adults ≥ 18 years of age with exclusion of positive ANA, diagnosis of RA, SLE, AS, or vasculitis, and at least one outpatient office visit during the study period. For both groups we excluded previous diagnosis of cancer prior to 2009. A chi-square test of association was performed between the 2 groups (AS patients and controls) and the odds ratio (OR), its standard error, and the 95% confidence interval (CI) were calculated. Results: Of the 14, 310 patients with AS, only 1300 (9.08%) patients had a cancer diagnosis compared to 2, 719, 240 controls (11.07%). The AS patients found to have decreased odds of cancer compared to control group (Odds ratio 0.9004, 95 % CI: 0.8502 to 0.9536, P = 0.0003). Demographics and clinical characteristic of AS patients and controls with cancer are shown in table 1. Risk factors for increased cancer risk in AS patients are shown in table 2. Conclusion: The study demonstrated that cancer risk was lower in the AS patients in the USA compared to the controls with no rheumatic disease. Male sex, white race, HLA-B27 positivity, history of IBD, NSAIDs use, and elevated makers of inflammation were associated with higher odds of cancer in AS patients. Acknowledgments: Dr. Yasir Tarabichi and Dr. David Kaelber Disclosure of Interests: Sali Merjanah: None declared, Mohamad Bittar: None declared, Marina Magrey Grant/research support from: AbbVie, Amgen, and UCB, Consultant of: Eli Lilly and Novartis